Effect of Structure on Oil-Water Separation Performance of Cylindrical Hydrocyclone - Jing Zhang, Xudong Jia, Fanchen Meng, Sheng Wang, Yonghua Gao, Liming Lin, Shiying Shi (Forest Chemicals Review)
As a new type of oil-water cyclone separation, cylindrical cyclone oil-water separator has many factors affecting its performance. In this paper, the influence of inlet structure is studied by numerical simulation. The results show that the diversion effect of different port structures is different, which affects the flow field distribution in the hydrocyclone. Among them, the effect of rectangular spiral inlet diversion is the best. At the same flow area, the separation efficiency of spiral hydrocyclone is the highest, and the separation efficiency of circle is slightly higher than that of rectangle. The numerical simulation shows that the upper position of the inlet is conducive to oil-water separation